Pengawasan Terhadap Alat Peraga Kampanye Dalam Penyelenggaraan Pemilu - Nurlaili, Maulida Resti; Alfons, Saartje Sarah; Soplantila, Ronny (Jurnal Saniri, 2024)
This article examines the implementation of supervision by the General Election Supervisory Agency (Bawaslu) in the 2024 Presidential and Vice Presidential Elections, especially in the implementation of the campaign. The campaign period in holding elections is one of the important stages in political contestation so it is vulnerable to violations, especially when its implementation involves many parties and the masses.  The campaign violations that often occur are administrative violations. Republic of Indonesia General Election Supervisory Agency Regulation Number 11 of 2023 concerning Supervision of General Election Campaigns. According to Law Number 7 of 2017 concerning General Elections, it is stated that general elections, hereinafter referred to as Elections, are a means of implementing people's sovereignty which is carried out directly, publicly, freely, confidentially, honestly and fairly in the Unitary State of the Republic of Indonesia based on Pancasila and the Constitution of the Republic of Indonesia. Indonesia in 1945. In the implementation of elections, many violations were found. It is not surprising that the Central Bawaslu and Panwaslu in the regions have a lot of evidence of violations committed by election organizers, participants and implementers.The method used in this research is normative juridical using a statutory approach and a conceptual approach. The sources of legal materials used in this research are primary legal materials, secondary legal materials and tertiary legal materials.Based on the results of this research, it shows that in carrying out supervision, the General Election Supervisory Body prevents violations and takes action against violations in synergy with supervision carried out at the district/city level. By focusing on the function of preventing violations, the General Election Supervisory Body prepares supervision plans based on potential vulnerabilities based on sub-stages and regions and intensively carries out outreach to the public and coordinates with stakeholders.  Meanwhile, in its enforcement function, the General Election Supervisory Body collaborates with the General Election Commission (KPU), the police and the prosecutor's office. The legal consequences for campaign violators are that they can be subject to administrative sanctions in the form of warnings and even removal of props. Sanctions include imprisonment for a minimum of 15 days or a maximum of 3 months and/or a fine of at least 100,000.00 (one hundred thousand rupiah), or a maximum of Rp. 1,000,000.00 (one million rupiah).